Linking Hydrogen (δ2H) Isotopes in Feathers and Precipitation: Sources of Variance and Consequences for Assignment to Isoscapes - Hobson, Keith A.; Van Wilgenburg, Steven L.; Wassenaar, Leonard I.; Larson, Keith (PLOS ONE, 2012)
Background Tracking small migrant organisms worldwide has been hampered by technological and recovery limitations and sampling bias inherent in exogenous markers. Naturally occurring stable isotopes of H (δ2H) in feathers provide an alternative intrinsic marker of animal origin due to the predictable spatial linkage to underlying hydrologically driven flow of H isotopes into foodwebs. This approach can assess the likelihood that a migrant animal originated from a given location(s) within a continent but requires a robust algorithm linking H isotopes in tissues of interest to an appropriate hydrological isotopic spatio-temporal pattern, such as weighted-annual rainfall. However, a number of factors contribute to or alter expected isotopic patterns in animals. We present results of an extensive investigation into taxonomic and environmental factors influencing feather δ2H patterns across North America. Principal Findings Stable isotope data were measured from 544 feathers from 40 species and 140 known locations. For δ2H, the most parsimonious model explaining 83% of the isotopic variance was found with amount-weighted growing-season precipitation δ2H, foraging substrate and migratory strategy. Conclusions/Significance This extensive H isotopic analysis of known-origin feathers of songbirds in North America and elsewhere reconfirmed the strong coupling between tissue δ2H and global hydrologic δ2H patterns, and accounting for variance associated with foraging substrate and migratory strategy, can be used in conservation and research for the purpose of assigning birds and other species to their approximate origin.